2018
DOI: 10.1111/jcmm.13717
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine deiminase 4 concentration, but not PADI4 polymorphisms, is associated with ICU mortality in septic shock patients

Abstract: The objective of our study was to evaluate the association between peptidylarginine deiminase 4 (PAD4) concentration and its polymorphisms with mortality in patients with septic shock. We prospectively evaluated 175 patients aged over 18 years with septic shock upon intensive care unit (ICU) admission. However, 48 patients were excluded. Thus, 127 patients were enrolled in the study. At the time of the patients’ enrollment, demographic information was recorded. Blood samples were taken within the first 24 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…Despite this, we did not observe a difference in the concentration of PAD4 between the individuals in whom AKI developed and those who died. This response is different from what we found in our previous study, with the same dataset, in which PAD4 concentration was associated with increased mortality in patients with septic shock [15]. This different performance of PAD4 as a biomarker suggests that PAD4 concentration is more important in sepsis than in AKI pathophysiology.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite this, we did not observe a difference in the concentration of PAD4 between the individuals in whom AKI developed and those who died. This response is different from what we found in our previous study, with the same dataset, in which PAD4 concentration was associated with increased mortality in patients with septic shock [15]. This different performance of PAD4 as a biomarker suggests that PAD4 concentration is more important in sepsis than in AKI pathophysiology.…”
Section: Discussioncontrasting
confidence: 99%
“…Ham et al [14], demonstrated that PAD4 plays an important role in a model of renal ischemia-reperfusion injury by increasing tubular inflammatory response. Based on previous data published by our group, using the same dataset, higher PAD4 concentrations were associated with lower ICU survival in patients with septic shock [15].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Received: January 22, 2019 Revised: July 28, 2019 Accepted: September 4, 2019 Published: October 15, 2019 Brodziak et al, 2013;Chen et al, 2014;Costa et al, 2018;Grasberger et al, 2013;Haber et al, 2017;Han et al, 2013;Hosokawa, 2008;Huang et al, 2015;MacMicking, 2004;Mihara et al, 2016;Ozato et al, 2008;Toyonaga et al, 2015;van der Meer-van Kraaij et al, 2007;Wang et al, 2011;Williams et al, 2015;Yuan et al, 2018.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…This includes cancer, chronic, autoimmune and neurodegenerative diseases [ 19 , 20 , 23 ], CNS injury [ 24 , 25 , 26 ] and ageing [ 27 , 28 ]. Importantly, roles for PADs have been described in viral [ 29 , 30 , 31 ] and other pathogenic infections, including sepsis, endotoxemia [ 29 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and antibiotic resistance [ 39 ]. The roles for PADs in anti-viral responses include PAD-mediated neutrophil extracellular trap formation (NETosis), for example, in respiratory syncytial virus disease [ 40 ].…”
Section: Introductionmentioning
confidence: 99%